Franchising Strategy for Strengthening Brand Equity at Janji Jiwa Coffee Shop - Fauzan Adhimah (Penerbit Goodwood, 2026)
Purpose: This study analyzes the effectiveness of franchising strategy as a tool for strengthening brand identity and accelerating business growth at Kopi Janji Jiwa in Indonesia’s food and beverage sector. Research Methodology: This research uses a qualitative descriptive approach through document analysis, field observations, and in-depth interviews with franchise management and business partners. Data were analyzed thematically to identify key strategic patterns in brand strengthening and outlet expansion. Results: The findings indicate that Janji Jiwa’s franchising strategy significantly strengthens brand competitiveness through consistent visual identity, standardized taste quality, intensive partner training, trend-driven menu innovation, and digital promotion. Strategic location selection based on market analysis also enhances brand penetration and accelerates outlet network expansion. These elements jointly contribute to increasing customer loyalty and expanding market reach. Conclusions: The franchising model implemented by Janji Jiwa successfully expands its business network, strengthens brand identity, and builds long-term customer loyalty. A structured operational system, strong partner support, and continuous innovation are key success factors. Limitations: This study is limited to a single brand case, so the results cannot be fully generalized to all franchise businesses. Contribution: This research provides practical insights for franchise business actors in designing sustainable brand strengthening strategies through standardized systems, partner empowerment, and innovation management.